Digital Humanities Workshops Lessons Learned - Estill, Laura; Guiliano, Jennifer (Digital Research in the Arts and Humanities, 2023)
Digital Humanities Workshops is the first volume to focus explicitly on the most common and accessible kind of training in digital humanities (DH): workshops. Drawing together the experiences and expertise of dozens of scholars and practitioners from a variety of disciplines and geographical contexts, the chapters in this collection examine the development, deployment, and assessment of a workshop or workshop series. In the first section, "Where?", the authors seek to situate digital humanities workshops within local, regional, and national contexts. The second section, "Who?", guides readers through questions of audience in relation to digital humanities workshops. In the third and final section, "How?", authors explore the mechanics of such workshops. Taken together, the chapters in this volume answer the important question: why are digital humanities workshops so important and what is their present and future role? Digital Humanities Workshops examines a range of digital humanities workshops and highlights audiences, resources, and impact. This volume will appeal to academics, researchers and postgraduate students, as well as professionals working in the DH field.